Delayed localized hypersensitivity reactions to COVID‐19 mRNA vaccines: a 6‐month retrospective study. (26th August 2021) - Papadimitriou, I.; Bakirtzi, K.; Sotiriou, E.; Vakirlis, E.; Hatzibougias, D.; Ioannides, D.
Abstract : Several individuals have developed delayed localized cutaneous vaccine reactions to the two novel mRNA Covid‐19 vaccines. Clinical and histopathologic results of this case series study confirm that the localized injection‐site reactions to the mRNA COVID‐19 vaccines are delayed hypersensitivity reactions that, unlike immediate hypersensitivity reactions, are not a contraindication to vaccination.